2014 International Symposium on Discharges and Electrical Insulation in Vacuum (ISDEIV) 2014
DOI: 10.1109/deiv.2014.6961628
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of grooved surface suppressing multipactor across HPM dielectric window

Abstract: Microwave breakdown phenomenon across dielectric window at the vacuum/dielectric interface limits the transmission of HPM and becomes a bottleneck of HPM technology development. Its avoidance or suppression is a major concern among researchers on HPM sources. Currently, the most effective approach is geometrical modification with the goal of altering the trajectories of electrons. In this paper, periodic rectangular grooves perpendicular to microwave electric field, are applied to improve the threshold of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Chang et al [20] and Huo et al [21] studied the multipactor of the grooved surface with simulation, indicating that grooves can significantly enhance the surface strength of the dielectric. Similar studies have also been conducted by Song et al [22]. Surface roughness has been studied systematically by Guo et al [14], it is shown that both SEE and the surface charge accumulation are remarkably inhibited on a roughened surface.…”
Section: Introductionsupporting
confidence: 70%
“…Chang et al [20] and Huo et al [21] studied the multipactor of the grooved surface with simulation, indicating that grooves can significantly enhance the surface strength of the dielectric. Similar studies have also been conducted by Song et al [22]. Surface roughness has been studied systematically by Guo et al [14], it is shown that both SEE and the surface charge accumulation are remarkably inhibited on a roughened surface.…”
Section: Introductionsupporting
confidence: 70%
“…In previous studies, a regular groove on the dielectric has been proved to be efficient in mitigating SEY [27,52,53]. In addition, it has been found that the groove parameter ought to be smaller than the critical parameter of collision distance λ min so that an avalanche cannot develop on the groove bottom and side walls [54]. The notion of λ min is also valid in our context.…”
Section: Theoretical Analysis and Experimental Supportmentioning
confidence: 51%
“…In the former stage flashover voltage increases with surface roughness, while in the latter stage flashover voltage decreases with roughness. Such a notion of 'critical size', above which the surface microstructure fails to mitigate the surface multipactor, was also reported in a previous high power microwave test of a di electric window [43]. In addition, the influence of roughness was previously included in modelling secondary electron emission (SEE), where Vaughan introduced the 'smoothness factor' in his empirical formula to represent surface condition [44].…”
Section: Theoretical Analyses and Simulation Modellingmentioning
confidence: 83%